140k views
2 votes
Cy+3=6d-2y solve for y

2 Answers

1 vote

remember that you can do anything to an equation as long as you do it to both sides

try to get the variable by itself on one side


Cy+3=6d-2y

minus 3 from both sides

Cy=6d-2y-3

add 2y to both sides

Cy+2y=6d-3

factor out the y

y(C+2)=6d-3

divide both sides by (C+2)


y=(6d-3)/(C+2)

User Abishek Aditya
by
5.6k points
1 vote

Cy+3=6d-2y

add 2y to each side

Cy +2y +3 = 6d

subtract 3 from each side

Cy +2y = 6d-3

factor out y

y(C+2) =6d-3

divide by (C+2) on each side

y = (6d-3)/(C+2)

User Don Hatch
by
4.8k points